Whole Genome Scan and Selection Signatures for Climate Adaption in Yanbian Cattle - Shen, Jiafei; Hanif, Quratulain; Cao, Yang; Yu, Yongsheng; Lei, Chuzhao; Zhang, Guoliang; Zhao, Yumin (Frontiers in Genetics, 2020)
Yanbian cattle is inhabitant of North of China, exhibiting many phenotypic features, such as long, dense body hair and abundant intramuscular fat, designed to combat the extreme cold climate adaption. In the current study, we studied the cold tolerance of nine Yanbian cattle by whole genome resequencing and compared with African tropical cattle, N’Dama, as a control group. Yanbian cattle was aligned to the Bos taurus reference genome (ARS-UCD1.2) yielding an average of 10.8 fold coverage. The positive selective sweep analysis for the cold adaption in Yanbian cattle were analyzed using Composite Likelihood Ratio (CLR) and nucleotide diversity (θπ), resulting in 292 overlapped genes. . The strongest selective signal was found on chromosome 16 with potential mutation in CORT gene, a regulatory gene of primary hormone in the hypothalamic-pituitary-adrenal (HPA) axis, is reported to be associated with the cold stress, represented 4 missense mutations (c.269C>T, p.Lys90Ile; c.251A>G, p.Glu84Gly; c.112C>T, p.Pro38Ser; c.86G>A, p.Pro29His). Meanwhile another gene on chromosome 6, showed significantly higher selective sweep signals for a cold adapted trait for hair follicle and length development, FGF5 (fibroblast growth factor 5) with a missense mutation (c.191C>T, p.Ser64Phe). Moreover, cold adapted Yanbian cattle was statistically compared with the hot adapted N’Dama cattle, using XP-CLR, Fst and θπ ratio, yielding 487, 924 and 346 genes respectively. Amongst the 12 overlapped genes, (CD36) (c.638A>G, p.Lys 213Arg) involved in fat digestion and absorption plays an important role in membrane transport of long-chain fatty acid and its expression could increase in cold exposure. Henceforth, Our study provides a novel genetic insights into the cold climate adaptation of Yanbian cattle and identified three candidate genes (CORT, and FGF5 and CD36), which can add to an understanding of the cold climate adaptation of Yanbian cattle.